Motivasi Kerja Sumber Daya Manusia dalam Organisasi: Sebuah Tinjauan Pustaka - Febrina, Intan; Rahmat, Hayatul Khairul (Journal of Current Research in Humanities, Social Sciences, and Business, 2024)
This study aims to study: the definition of work motivation, the approach to work motivation, the purpose of work motivation, the driving factors, and the view of work motivation in organizations. This study used a literature study method. The findings of this study were that motivation has forms such as intentions, hopes, desires, and goals to be achieved. In addition, the purpose of work motivation is to give encouragement to oneself and have an impact on colleagues, increase cooperation between colleagues, increase personal and group discipline, foster a good work atmosphere, improve organizational welfare, increase the sense of responsibility in each employee. There are also several views or models of motivation in organizations, namely the traditional model, the human relationship model, and the human resources model.